Integrated transport and land use planning the facts, fiction, fallacies and future of the government's integrated transport and land use planning strategies - plus answers to a good few mysteries. (Thomas Telford, 2002)
Presents a report which provides an objective and constructive critique of the Government's transport and land use policies. This book is an interesting read for transport planners engineers, architects, politicians, and the public at large.